Perbandingan Pengaturan Tindak Pidana Perzinaan dalam KUHP Lama, KUHP Baru, dan Hukum Pidana Islam - Mizaj Zanjabila Haq; Carlos Afonso Barreto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2026)
Abstract This article examines the legal regulation of adultery in three different legal frameworks: the Indonesian Criminal Code 2023, the former colonial Criminal Code (WvS), and Islamic criminal law. The 2023 Criminal Code expands the definition of adultery compared to the old code, which limited adultery to married individuals. Islamic criminal law, on the other hand, places adultery as a serious offense within the category of hudud with strict evidentiary requirements. This comparative study highlights the differences in legal orientation, societal values, and philosophical foundations of each regulatory system. Ultimately, the study argues that changes in adultery regulation reflect broader moral, social, and political dynamics in Indonesian society.